Commercial action based on information management in a small IT company (Journal of Information Systems and Technology Management, 2008)
This research proposes to define models for information management to guide the commercial action of a small IT company. The focus on small companies occurs due to the high percentage of companies with this profile in the IT sector. A set of models for information management was proposed, implemented and used during the daily commercial activities. The practical experience is detailed based on the evaluation of ease, comprehension and use. Action research was chosen as a methodology for this study because there was interest and availability of the company to put into practise the new set of models that was proposed. The company reacted positively do the models that were implemented, in terms of acceptance and in terms of comprehension, ease of use and utility. The company considered that, after using the models, there were better conditions of handling the information, and, therefore, it became possible to guide the commercial action in a more dynamic way.